Anti-tumor Activity of Toll-Like Receptor 7 Agonists - Chi, Huju; Li, Chunman; Zhao, Flora Sha; Zhang, Li; Ng, Tzi Bun; Jin, Guangyi; Sha, Ou (Frontiers in Pharmacology, 2017)
Toll like receptors (TLRs) are a class of pattern recognition receptors that play a bridge role in the innate immunity and adaptive immunity. The activated TLRs not only induce inflammatory responses, but also lead to the development of antigen specific immunity. TLR7, a member of TLR family, is an intracellular receptor expressed on the membrane of endosomes, and its powerful immune stimulatory action can be potentially used in the anti-tumor therapy. This article reviews the anti-tumor activities of the agonists of TLR7, which are frequently applied in the preclinical and clinical investigations.